State-of-the-Practice in Connecting and Coordinating Transportation and Land Use Planning in the U.S.A. Issue 9 (September 2019) - Sabouri, Sadegh; Dillon, Amanda; Proffitt, David; Townsend, Megan; Ewing, Reid
Metropolitan planning organizations (MPOs) providing funding for local land use planning is part of a growing trend which has so far received very little attention. This study surveyed a stratified sample of 30 U.S. MPOs weighted toward larger metropolitan areas. Of the 30 MPOs, about half were funding smart growth-oriented local land use planning through transportation and land use connection (TLC) programs. From them, 10 MPOs with TLC programs were selected and written up as case studies. Across the case studies it was found that the funding and support provided differs greatly by region. The ultimate goal of these programs was similar, however—to reduce suburban sprawl and the associated need for highway building, and instead to create more livable, sustainable, walkable, bikeable, and transit-accessible communities within the region. These gaols were achieved by promoting infill and development in and around urban centers, and encouraging concentration of activity around transit stations. With the exception of one program, funding portfolios have grown year by year. While project funding selection criteria differ across MPOs, how well they align with the region's transportation plan seems to be of paramount importance.